Biochemical bone markers in children with steroid sensitive nephrotic syndrome in remission - Sinha, Neha; Wade, Poonam; Ghildiyal, Radha Gulati; Maniar, Hemil (International Journal of Contemporary Pediatrics, 2018)
Background: Glucocorticoids, the recommended first line treatment of steroid sensitive nephrotic syndrome (SSNS), are notorious for causing osteoporosis. There are very few studies from tropical countries looking at the lasting effects of a short course of glucocorticoids in SSNS. The objective is to study the effect of glucocorticoids and its dose on Vitamin D levels and biochemical markers of calcium metabolism in children with SSNS and to formulate a criterion to administer prophylactic calcium and vitamin D supplementation to such patients. Methods: A cross-sectional case-control study was conducted on 30 children with SSNS in remission and 30 healthy controls. Serum levels of 25 hydroxycholecalciferol [25(OH)D], calcium, phosphorous, albumin, alkaline phosphatase (ALP) and intact parathyroid (PTH) were measured. Total glucocorticoid exposure during the illness was summarized. Results: Children with SSNS had significantly lower height [median-100.00 (interquartile range IQR- 14.5) vs. controls [115.50 (17.5)] cm; P= 0.0003. Serum ALP levels was significantly higher in the cases [median 264 (IQR-80.7)] IU/L vs. controls [median 234 (IQR- 132)] IU/L; P= 0.028. Though hypovitaminosis D was universal in the study cohort; children with SSNS had worse Vitamin D status (76.7%) than healthy controls (50%). Levels of serum calcium, phosphorous, vitamin D and PTH were not significantly different between the two groups, nor were they related to total cumulative dose of steroid. Vitamin D levels showed no significant co-relation with number of relapses, age, calcium, phosphate, ALP, or PTH levels. Conclusions: Children with SSNS may benefit from routine measurement of 25 (OH) D and prophylactic supplementation with calcium and Vitamin D.